2014
DOI: 10.1080/10496475.2014.940437
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Bioactive Potential of Dehydrated Peels ofBenincasa hispida, Luffa acutangula, andSechium edule

Abstract: Dehydrated peels from ash gourd ( Benincasa hispida), ridge gourd ( Luffa acutangula), and cho-chow marrow ( Sechium edule) were analyzed for chemical composition and bioactive potential. The range of constituents per 100g dry peels were protein, 3 to 15 g; insoluble fiber, 45 to 58 g; ether extractives, 2.3 to 3.3 g; iron, 5.1 to 17.4 mg; calcium, 307 to 704 mg; tannins, 580 to 848 mg; carotenoids, 1,712 to 35,663 μg; and ascorbic acid, 37 to 51 mg. Polyphenols, total antioxidant activity, free radical scaven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 20 publications
2
8
0
Order By: Relevance
“…These observations were in agreement with Yoshimura [ 11 ] who reported that the chayote fruit contains 4.03% DM, and the DM contained 16.26% CP, 1.17% EE, 7.31% CF, 68.39% NFE, and 6.86% total ash, respectively. Similar observations were also observed by Nagarajaiah and Prakash [ 12 ] in S. edule dehydrated peels in which 100 g contained 15.15 g proteins, 45.24 g insoluble fiber, and 2.32 g EE.…”
Section: Resultssupporting
confidence: 89%
“…These observations were in agreement with Yoshimura [ 11 ] who reported that the chayote fruit contains 4.03% DM, and the DM contained 16.26% CP, 1.17% EE, 7.31% CF, 68.39% NFE, and 6.86% total ash, respectively. Similar observations were also observed by Nagarajaiah and Prakash [ 12 ] in S. edule dehydrated peels in which 100 g contained 15.15 g proteins, 45.24 g insoluble fiber, and 2.32 g EE.…”
Section: Resultssupporting
confidence: 89%
“…Vitamins present in the edible portion (per 100 g) of this plant are vitamin C (1.35-68.00), thiamin (0.02-0.04), riboflavin (0.02-0.31), niacin (0.20-0.46), and vitamin E. Major minerals in the edible portion (per 100 g) include sodium (0.14-6.00), potassium (77.00-131.00), calcium (5.00-23.32), iron (0.20-0.49), and phosphorus (225.39-234.61) [ 6 , 16 , 17 ]. The fruit contains water-soluble polysaccharides [ 18 ], such as arabinogalactans [ 19 ].…”
Section: Botany and Traditional Usesmentioning
confidence: 99%
“…Nagarajaiah and Prakash (2014) evaluated physical characteristics and the chemical composition of the dehydrated fruit peel. The results exhibited the presence of iron (4.74 mg), calcium (416 mg), phosphorous (233 mg), ascorbic acid (35 mg) (49) , carotene (36.96 mg) (50) and tannin (778.20 mg) per 100 gm of peel (Figure 6) (Nagarajaiah and Prakash, 2014).…”
Section: Phytochemistrymentioning
confidence: 99%
“…The results exhibited the presence of iron (4.74 mg), calcium (416 mg), phosphorous (233 mg), ascorbic acid (35 mg) (49) , carotene (36.96 mg) (50) and tannin (778.20 mg) per 100 gm of peel (Figure 6) (Nagarajaiah and Prakash, 2014). …”
Section: Phytochemistrymentioning
confidence: 99%